MENGOPERASIKAN MICROSOFT WORD DAN DASAR-DASAR PENYUNTINGAN DALAM MICROSOFT WORD UNTUK DATA KESEHATAN - Relfi Alfebrian Pasaribu; Alex Gunawan Zamasi; Mohamad Arif Dingkol; Cahaya Amalia Trangen; Marsya Adelia Lolung; Alya Putri Fadhilah Limbanadi; Sri Nayla Paputungan; Lala Ghiva Korompot; Anastasya Mamonto; Naila Azzahra Paputungan; Ameliya Legoh (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Microsoft Word is a word processing application widely used for creating, editing, and formatting text documents. This journal aims to explain the basics of operating and editing documents in Microsoft Word, from creating a new document, editing text, to formatting documents. The steps discussed include how to create a new document, edit and revise text, use the copy, cut, and paste features, as well as adjust text and paragraph formatting. In addition, this journal also covers the use of additional features such as spell check, track changes, and the insertion of images or tables. Through understanding these basics, users can utilize Microsoft Word more efficiently to produce well-structured and professional documents.